Treating leishmaniasis in Amazonia, part 2: Multi-target evaluation of widely used plants to understand medicinal practices. (10th May 2022) - Houël, Emeline; Ginouves, Marine; Azas, Nadine; Bourreau, Eliane; Eparvier, Véronique; Hutter, Sébastien; Knittel-Obrecht, Adeline; Jahn-Oyac, Arnaud; Prévot, Ghislaine; Villa, Pascal; Vonthron-Sénécheau, Catherine; Odonne, Guillaume
Abstract: Ethnopharmacological relevance: Leishmaniasis are widely distributed among tropical and subtropical countries, and remains a crucial health issue in Amazonia. Indigenous groups across Amazonia have developed abundant knowledge about medicinal plants related to this pathology. Aim of the study: We intent to explore the weight of different pharmacological activities driving taxa selection for medicinal use in Amazonian communities. Our hypothesis is that specific activity against Leishmania parasites is only one factor along other (anti-inflammatory, wound healing, immunomodulating, antimicrobial) activities. Materials and methods: The twelve most widespread plant species used against leishmaniasis in Amazonia, according to their cultural and biogeographical importance determined through a wide bibliographical survey (475 use reports), were selected for this study. Plant extracts were prepared to mimic their traditional preparations. Antiparasitic activity was evaluated against promastigotes of reference and clinical New-World strains of Leishmania ( L. guyanensis, L. braziliensis and L. amazonensis ) and L. amazonensis intracellular amastigotes. We concurrently assessed the extracts immunomodulatory properties on PHA-stimulated human PBMCs and RAW264.7 cells, and on L. guyanensis antigens-stimulated PBMCs obtained from Leishmania -infected patients, as well as antifungal activity and wound healing properties (human keratinocyte migration assay) of the selected extracts. The cytotoxicity of the extracts against various cell lines (HFF1, THP-1, HepG2, PBMCs, RAW264.7 and HaCaT cells) was also considered. The biological activity pattern of the extracts was represented through PCA analysis, and a correlation matrix was calculated. Results: Spondias mombin L. bark and Anacardium occidentale L. stem and leaves extracts displayed high anti-promatigotes activity, with IC50  ≤ 32 μg/mL against L. guyanensis promastigotes for S. mombin and IC50 of 67 and 47 μg/mL against L. braziliensis and L. guyanensis promastigotes, respectively, for A. occidentale . In addition to the antiparasitic effect, antifungal activity measured against C. albicans and T. rubrum (MIC in the 16–64 μg/mL range) was observed. However, in the case of Leishmania amastigotes, the most active species were Bixa orellana L. (seeds), Chelonantus alatus (Aubl.) Pulle (leaves), Jacaranda copaia (Aubl.) D. Don. (leaves) and Plantago major L. (leaves) with IC50  < 20 μg/mL and infection rates of 14–25% compared to the control. Concerning immunomodulatory activity, P. major and B. orellana were highlighted as the most potent species for the wider range of cytokines in all tested conditions despite overall contrasting results depending on the model. Most of the species led to moderate to low cytotoxic extracts except for C. alatus, which exhibited strong cytotoxic activity in almost all models. None of the tested extracts displayed wound healing properties. Conclusions: We highlighted pharmacologically active extracts either on the parasite or on associated pathophysiological aspects, thus supporting the hypothesis that antiparasitic activities are not the only biological factor useful for antileishmanial evaluation. This result should however be supplemented by in vivo studies, and attracts once again the attention on the importance of the choice of biological models for an ethnophamacologically consistent study. Moreover, plant cultural importance, ecological status and availability were discussed in relation with biological results, thus contributing to link ethnobotany, medical anthropology and biology. Graphical abstract: Image 1